Rotational priority investigation in fuzzy analytic hierarchy process design: An empirical study on the marine engine selection problem - Bulut, Emrah; Duru, Okan; Kocak, Gazi (ELSEVIER SCIENCE INC, 2015)
The aim of this paper is to improve the applicability of the fuzzy-AHP method by using the rotational priority investigation (RPI) method. Despite its popularity and convenience, the AHP and fuzzy-AHP method is criticized by many scholars because of intransitivity and the rank reversal phenomenon. Experts may question the rational choice theory and cross priorities may indicate conflicting interactions. Also, the extraction of a number of alternatives may cause a different order of priorities. The rotational priority investigation method is proposed to investigate sub-group priorities and their corresponding rankings. Every rotation refers to the investigation of sub-group priorities after extraction of an alternative. The final result is based on the normalized average priority among the several rotations. An empirical study is presented by using the RPI method in the fuzzy AHP for the marine engine selection problem in the shipping industry. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Fuzzy-AHP; Rational choice theory; Rank reversal; Marine engine; CONSISTENCY INDEX; AHP; PRIORITIZATION; TOPSIS; MODEL; Engineering; Mathematics; Mechanics